IMPLEMENTASI PROGRAM KELUARGA HARAPAN DI KECAMATAN RANOYAPO KABUPATEN MINAHASA SELATAN - MANDOLANG, YOSUA; LENGKONG, FLORENCE DAICY; DENGO, SALMIN (JURNAL ADMINISTRASI PUBLIK, 2019)
Family Expectations Program implementation in Ranoyapo Regency of Minahasa in the South.Family Expectations Program implementation aimed to improve, welfare Families Beneficiaries throughaccess to education, health services, social welfare, and reduce the burden of spending and increase familyincome the poor and vulnerable, creating behavior change and independence Family Beneficiaries inaccessing health and education services as well as reducing poverty and inequalities, promoting the benefitsof formal financial products and services to the family Beneficiaries. In the implementation of theprogramme, has not been able to walk to the maximum. Therefore, the proposed research is to answer thequestion about Family Expectations Program implementation in South Minahasa Regency Ranoyapo. Inthis study the researchers used a model implementation of George c. Edward III, the implementation of thepolicy views of 4 variables that affect the implementation of the policy. Communication is an importantfactor in the success of a policy, including command and decision-making. Adequate resources eitherhuman resources or financial resources will have an impact on the degree of success of a policy. Thedisposition is the attitude that is owned by the application of ethics policy and commitment to making thispolicy work. Bureaucratic structure, namely the extent to which a range of control between leadership andsubordinate in implementing organizational structure. In this research uses qualitative research methods,descriptive, i.e. through interviews to 12 informants in direct observation, and search for documents relatedto the program, even before the study guidelines helped interview , and stationery to write. The results ofthis research are generally explained that the implementation of the Family Hope Program in SouthMinahasa Regency Ranoyapo has not run optimally.Keywords: implementation of policy, program, the family of hope